ANALYSIS OF THE USE OF DEXIS IN SPOKEN DISCOURSE A CASE STUDY OF THE BMKG HEAD'S INTERVIEW ON THE MEGATRUST EARTHQUAKE WARNING - Putri Apika Sari; Ngusman Abdul Manaf; Tressyalina (JURNAL KONFIKS, 2026)
This research examines the use of deixis in oral discourse by analyzing the interview transcript of the Head of BMKG, Dwikorita Karnawati, regarding megathrust earthquake warnings in Indonesia. Deixis is a linguistic phenomenon whose reference depends on the context of utterance, encompassing person, place, time, discourse, and social deixis. The research aims to: (1) identify types of deixis used in the interview; (2) analyze the pragmatic functions of deixis in formal institutional discourse context; and (3) explain how deixis contributes to communication effectiveness and authority construction in interviews. This research employs a qualitative descriptive method with data from a 30-minute interview transcript. Analysis was conducted using the deixis theory framework from Levinson (1983) and Yule (1996). The results show that: (1) all five types of deixis were found in the interview with high frequency: person deixis (245 times), place deixis (78 times), time deixis (62 times), discourse deixis (45 times), and social deixis (38 times); (2) person deixis is predominantly used with variations reflecting formal relationships between interviewer and interviewee; (3) place and time deixis function to concretize technical information about megathrust locations and earthquake occurrence periods; (4) discourse deixis plays an important role in creating cohesion between turns; (5) social deixis through formal address terms and pronouns contributes to authority and professionalism construction. This research contributes to understanding Indonesian pragmatics in formal institutional discourse contexts.